Agricultural head rents, pre-famine and post-famine - Grada, CO (Economic & Social Studies, 1974)
'No country can ever be held in just estimation', proclaimed Arthur Young in 1780, 'when the rental of it is unknown': and Young , in his Tour in Ireland, proceeded to estimate the rental of this country. His was the rhetoric of the political arithmetician, but he was neither the first nor the last to embark on aggregate calculations. Several of the best-known past observers of the Irish scene, from Sir William Petty to the elder Wakefield, also left their o w n estimates. Some, like Wakefield's, were carefully worked out; others, such as Dean Swift's, were based almost totally on hearsay or speculation.
Keywords: Rent; Agriculture; Ireland